Intra- and Interspecies Wing Venation Variations of Apis cerana and Apis nigrocincta Species in Indonesia - Nisfia Rakhmatun Nisa; Berry Juliandi; Rika Raffiudin; Jauharlina Jauharlina; Mahardika Gama Pradana; Araz Meilin; Jasmi Jasmi; Yulia Pujiastuti; Puji Lestari; Fahri Fahri; Windra Priawandiputra; Tri Atmowidi (HAYATI Journal of Biosciences, 2022)
Apis cerana has a wide distribution in Asia, including Sundaland, and is currently found in Wallacea, while the sister species, A. nigrocincta, is native in Sulawesi. The wide geographic distribution and the island isolation led to form morphological differences in the bees. The morph and wing venations are known to have a high genetic inheritance. Therefore, this research aimed to (1) analyze the landmark variation of wing venations of A. cerana from Sundaland and Wallacea, and A. nigrocincta from Sulawesi, (2) determine the relationship between these two bee species. The research was conducted by digitizing 550 wing venations based on nineteen landmarks. Our study on intraspecies showed that A. cerana Sumatra revealed a high variation in bending energy. Overall, the deformation grid of A. cerana from Sundaland has higher displacement than those from Wallacea, meaning higher variations of the Sundaland A. cerana. We found geometric morphometric markers of landmarks 16 and 17 in intraspecies and interspecies bees. Thus, these landmarks known as a cubital index can be used for species identification. The differentiation of interspecies has been shown in the PCA. Apis nigrocincta was separated from the single group of the centroid A. cerana and was supported by the Neighbor-Joining tree.